Health Equity and Financial Protection in Malawi - World Bank (Washington, DC, 2017)
The health equity and financial protection reports are short country-specific volumes that provide a picture of equity and financial protection in the health sectors of low-and middle-income countries. Topics covered include: inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. Malawi's government is committed to improving equity and financial protection in the health sector. Equity is explicitly mentioned as one of the four objectives in the Health Sector Strategic Plan (HSSP). The overall objective of the HSSP is to contribute towards Malawi's attainment of the health and related millennium development goals. The specific objectives of the HSSP are, therefore, to: 1) increase coverage of the high quality Essential Health Package (EHP) services; 2) reduce risk factors to health; 3) improve equity and efficiency in the delivery of quality EHP services; and 4) strengthen the performance of the health system to support delivery of EHP services. Malawi spends 6.2 per cent (2009) of its gross domestic product (GDP) on health. This is similar to the average spending in other lower income countries in Africa, which have spent an average of 6.5 per cent (2009) of their GDP on health. The central Ministry of health is responsible for the development and enforcement of health policy, regulation of the health sector, creation of standards and norms, allocation and management of resources, provision of technical support, coordination, and monitoring and evaluation.